Feminizing Hormone Therapy Prescription Patterns and Cardiovascular Risk Factors in Aging Transgender Individuals in Australia - Balcerek, Matthew I.; Nolan, Brendan J.; Brownhill, Adam; Wong, Peggy; Locke, Peter; Zajac, Jeffrey D.; Cheung, Ada S. (Frontiers in Endocrinology, 2021)
Context: The safety and efficacy of feminizing hormone therapy in aging transgender (trans) individuals is unclear. Current recommendations suggest transdermal estradiol beyond the age of 45 years, especially if cardiometabolic risk factors are present. Objective: To evaluate feminizing hormone therapy regimens and cardiovascular risk factors in aging trans individuals. Design: Retrospective cross-sectional analysis. Setting: Primary care and endocrine specialist clinic in Melbourne, Australia. Participants: Trans individuals on feminizing therapy for ≥6 months. Main outcomes measures: Feminizing hormone regimens and serum estradiol concentrations by age group: (a) ≥45 years, (b) <45 years, and prevalence of cardiometabolic risk factors in individuals ≥45 years. Results: 296 individuals were stratified by age group: ≥45 years (n=55) and <45 years (n=241). There was no difference in median estradiol concentration between groups (328 nmol/L vs. 300 nmol/L, p=0.22). However, there was a higher proportion of individuals ≥45 years treated with transdermal estradiol (31% vs. 8%, p<0.00001). Of those treated with oral estradiol, the median dose was lower in the ≥45 years group (4mg vs. 6mg, p=0.01). The most prevalent cardiometabolic risk factor in the ≥45 years group was hypertension (29%), followed by current smoking (24%), obesity (20%), dyslipidaemia (16%) and diabetes (9%). Conclusions: A greater proportion of trans individuals ≥45 years of age were treated with transdermal estradiol. Of those who received oral estradiol, the median dose was lower. This is important given the high prevalence of cardiometabolic risk factors in this age group, however cardiovascular risk management guidelines in this demographic are lacking.